Validation of the Copenhagen Burnout Inventory in Pharmacists - Olajide O. Fadare; Michael Andreski; Matthew J. Witry (University of Minnesota Libraries Publishing, 2021)
Objectives: This study aimed to 1) determine the validity of the Copenhagen Burnout Inventory (CBI) for use in the assessment of burnout in a sample of pharmacists using confirmatory factor analysis (CFA), and 2) use the CBI items and other measures of work-life to assess burnout in pharmacists employed in various types of practice. Methods: A cross-sectional survey was administered to a sample of 2,582 pharmacists in a single Midwestern US state. The survey included the three subscales of the CBI, each of which measures personal, work-related, and patient-related dimensions of burnout. Other items included demographics, practice type, workload, and work-life balance. CFA was used to measure fit, and Cronbach's alpha was used to assess reliability. Correlation was used to assess criterion validity of the CBI. Logistic regression and bivariate analyses were used to assess pharmacist burnout based on demographics. Results: Following the removal of 2 items from the measurement model, a 17-item 3-factor CBI was found to possess satisfactory psychometric properties for use in pharmacists. The CBI correlated with measures of work-life demonstrating criterion validity. A logistic regression showed that younger pharmacists and community pharmacists experience higher burnout than older pharmacists and clinical pharmacists. Community pharmacists also more often reported high workloads and poorer work-life integration. Both community and clinic pharmacists desired more time providing patient care services and less time dispensing. Conclusion: The CBI is a psychometrically reliable and valid instrument for assessing burnout in pharmacists. Younger pharmacists and community pharmacists warrant attention due to their higher degree of burnout.